Alcohol Alters the Activation of ERK1/2, a Functional Regulator of Binge Alcohol Drinking in Adult C57BL/6J Mice - Agoglia, Abigail E. (Alcohol Clin Exp Res, 2015)
BACKGROUND: Binge alcohol drinking is a particularly risky pattern of alcohol consumption that often precedes alcohol dependence and addiction. The transition from binge alcohol drinking to alcohol addiction likely involves mechanisms of synaptic plasticity and learning in the brain. The mitogen-activated protein kinase (MAPK) signaling cascades have been shown to be involved in learning and memory, as well as the response to drugs of abuse, but their role in binge alcohol drinking remains unclear. The present experiments were designed to determine the effects of acute alcohol on extracellular signaling related kinases (ERK1/2) expression and activity, and to determine whether ERK1/2 activity functionally regulates binge-like alcohol drinking. METHODS: Adult male C57BL/6J mice were injected with ethanol (3.0 mg/kg, IP) 10, 30 or 90 minutes prior to brain tissue collection. Next, mice that were brought to freely consume unsweetened ethanol in a binge-like access procedure were pretreated with the MEK1/2 inhibitor SL327 or the p38 MAP kinase inhibitor SB239063. RESULTS: Acute ethanol increased pERK1/2 immunoreactivity relative to vehicle in brain regions known to be involved in drug reward and addiction, including the central amygdala and prefrontal cortex. However, ethanol decreased pERK1/2 immunoreactivity relative to vehicle in the nucleus accumbens core. SB239063 pretreatment significantly decreased ethanol consumption only at doses that also produced nonspecific locomotor effects. SL327 pretreatment significantly increased ethanol, but not sucrose, consumption without inducing generalized locomotor effects. CONCLUSIONS: These findings indicate that ERK1/2MAPK signaling regulates binge-like alcohol drinking. Since alcohol increased pERK1/2 immunoreactivity relative to vehicle in brain regions known to regulate drug self-administration, SL327 may have blocked this direct pharmacological effect of alcohol and thereby inhibited the termination of binge-like drinking.